Risk stratification in children with cancer and febrile neutropenia: A national, prospective, multicentre validation of nine clinical decision rules. (January 2020) - Haeusler, Gabrielle M.; Thursky, Karin A.; Slavin, Monica A.; Babl, Franz E.; De Abreu Lourenco, Richard; Allaway, Zoe; Mechinaud, Francoise; Phillips, Robert; ,
Abstract: Background: Reduced intensity treatment of low-risk febrile neutropenia (FN) in children with cancer is safe and improves quality of life. Identifying children with low-risk FN using a validated risk stratification strategy is recommended. This study prospectively validated nine FN clinical decision rules (CDRs) designed to predict infection or adverse outcome. Methods: Data were collected on consecutive FN episodes in this multicentre, prospective validation study. The reproducibility and discriminatory ability of each CDR in the validation cohort was compared to the derivation dataset and details of missed outcomes were reported. Findings: There were 858 FN episodes in 462 patients from eight hospitals included. Bacteraemia occurred in 111 (12·9%) and a non-bacteraemia microbiological documented infection in 185 (21·6%). Eight CDRs exhibited reproducibility and sensitivity ranged from 64% to 96%. Rules that had >85% sensitivity in predicting outcomes classified few patients (<20%) as low risk. For three CDRs predicting a composite outcome of any bacterial or viral infection, the sensitivity and discriminatory ability improved for prediction of bacterial infection alone. Across all CDRs designed to be implemented at FN presentation, the sensitivity improved at day 2 assessment. Interpretation: While reproducibility was observed in eight out of the nine CDRs, no rule perfectly differentiated between children with FN at high or low risk of infection. This is in keeping with other validation studies and highlights the need for additional safeguards against missed infections or adverse outcomes before implementation can be considered.